Design, Fabrication and Performance Evaluation of Beans Dehuller (Journal of Science and Technology, 2016)
Abeans dehulling machine was designed and fabricated using a locally available materials. The performance of the machine was evaluated and the results showed that the higher the feed regulator opening the higher the dehulling rate. The average capacity of the dehulling machine is found to be 3.67kg/h and the efficiency also is 75.7%.